The equalization system of local budgets in Ukraine: effectiveness and pathways for improvement - Kaziuk , Yanina; Ventsel , Viktor (Pressing Problems of Public Administration, 2024)
The article is devoted to the analysis of the effectiveness of the financial equalization system in Ukraine and the development of proposals for its improvement in order to reduce disparities between territorial communities and ensure equal access of citizens to public services regardless of their place of residence. The authors consider the theoretical foundations of financial equalization, its functions and international experience, focusing on the requirements of the European Charter of Local Self-Government. Based on the analysis of statistical data on the volume and dynamics of basic and reverse subsidies, their share in GDP and local budget revenues, as well as indicators of differentiation of territories’ tax capacity before and after equalization, the authors conclude that the current system in Ukraine only partially fulfils its function. In particular, the volume of the basic subsidy is insufficient to ensure the financial capacity of all communities, and the gap between «rich» and «poor» territories remains excessive even after equalization. The article proposes a number of ways to improve the domestic model of financial equalization. Among them: expanding the list of payments taken into account when calculating subsidies; increasing the amount of funds allocated for equalization; introducing a multi-level equalization system with differentiation of calculations for different categories of communities; revising the fundamental principles of the system in the context of post-war recovery. The authors emphasize the need to develop new approaches to assessing the effectiveness of financial equalization in terms of its impact on the quality of life of community residents and the level of human and infrastructural capital of territories.